SEJARAH dan PERKEMBANGAN INTERNET DI INDONESIA - Alcianno Ghobadi Gani (JURNAL MITRA MANAJEMEN, 2013)
AbstractIndonesian internet history began in the early 1990s. At that time, Internet network inIndonesia is better known as a community network, where the spirit of cooperation,kinship and mutual cooperation is very warm and felt among the perpetrators. Somewhatdifferent from the atmosphere on the development of Indonesian Internet then that feelsmore commercial and individual in most activities, especially those involving Internetcommerce. Since 1988, there was an early user of the Internet in Indonesia that utilizeCIX (England) and CompuServe (U.S.) to access the Internet.